ЖАСЛАР АРАСЫНДА ЖЫНАЯТШЫЛЫҚТЫҢ АЛДЫН АЛЫЎДА МӘҲӘЛЛЕНИҢ ОРНЫ ҲӘМ РОЛИ - Реймбаев, А. (SCIENCE and SOCIETY, 2018)
The article is devoted to the role and importance of the institute of mahalla in prevention of crime among the youth.
Keywords: youth; self-government institutions of citizens; prevention of crime; experience; courtesy; education; decree; pedagogics